Sensory cue integration - Trommershauser, Julia; Kording, Konrad; Landy, Michael S. (Oxford : Oxford University Press, 2011)
This text is concerned with sensory cue integration both within and between sensory modalities, and focuses on the emerging way of thinking about cue combination in terms of uncertainty.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Computational neuroscience; Cognitive neuroscience; Senses and sensation